Bahasa Inggris - Ayulia Febrianti (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2025)
In an English classroom, classroom management is often associated with discipline and the regulation of student behavior to ensure order and focus. However, effective classroom management encompasses more than discipline, aiming to establish an environment conducive to achieving positive educational outcomes. This study explores the classroom management experiences and perceptions of 5th-semester English Department B Class students. As future educators, these students provide valuable insights into managing classroom dynamics and fostering student engagement. This qualitative phenomenological study adopts a descriptive approach, focusing on their strategies, challenges, and reflections in managing English classrooms. The findings emphasize the importance of developing facilitative skills, relationship-building techniques, and behavior management strategies early in teacher training. Effective teachers are those capable of employing tailored strategies to handle diverse classroom behaviors, from managing group dynamics to addressing individual student needs.